'If They can't do any Good, They shouldn't Come': Northern Evaluators in Southern Realities. Issue 2 (August 2013) - Jayawickrama, Janaka
Based on research and evaluation experiences from Sri Lanka, Malawi, Sudan and Pakistan, this paper reflects on critical implications of ethics at local level. Providing various examples, the paper invites the reader to think through solutions to their own questions and challenges in the realm of evaluation ethics. Further, this paper examines the ethics of evaluation through the lens of the author's own experiences as a researcher and evaluator, which is shaped by his particular positionality and by what he has learnt working in the space within and between the European university system and violently divided communities. From this standpoint, this paper has managed to distinguish some of the central challenges to evaluators working in violently divided communities.